Markers of chronic disease risk in term low birthweight Indian children aged 8–14 years - Gusain, Yamini; Malik, Anku; Filteau, Suzanne; Pathak, Renuka; Sachdev, Harshpal Singh; Trilok-Kumar, Geeta (Frontiers in Pediatrics, 2024)
Background: Low birth weight (LBW) is a public health problem in India with consequences in the short and long term. It increases the risk of obesity and its related comorbidities including type 2 diabetes and cardiovascular disease (CVD) in later life. This study aimed to assess the risk markers of chronic disease in term born low birthweight Indian children aged 8-14 years. Methods: This was a cross-sectional follow-up of LBW children from DIVIDS (Delhi Infant Vitamin D Supplementation) cohort and involved assessment of their anthropometric measurements, body composition, levels of adipokines and biomarkers of chronic diseases. Neighbourhood children born normal birth weight (NBW) (>2.5 kg) were enrolled for comparison.The study included 667 LBW and 87 NBW children. Height-for-age, body mass index for-age (BMIZ), fat-free mass index, and waist circumference of LBW children were lower than those of NBW children. LBW children could jump farther. LBW children who were now overweight had higher leptin, triglyceride and VLDL and lower HDL, compared to NBW children in the same BMIZ category. Currently underweight LBW children had higher adiponectin and lower leptin levels than the reference group. There were no differences between LBW and NBW children in visfatin, fasting glucose and insulin, hemoglobin A1c, triglyceride, low density lipoprotein or C-reactive protein.At 8-14 years few children were overweight and there were few differences in some risk markers of chronic disease between LBW and NBW children. Overweight, which was associated with some increased risk markers, may increase with age, thus timely counselling and monitoring of these LBW children will be important to mitigate these risks.